Food without fire: Environmental and nutritional impacts from a solar stove field experiment - McCann, Laura E.; Michler, Jeffrey D.; Mwangala, Maybin; Olurotimi, Osaretin; Estrada-Carmona, Natalia (Wiley, 2025)
Over 80% of the population in rural Sub‐Saharan Africa relies on biomass cooking fuel, a substantial source of anthropogenic greenhouse gases. We use a field experiment in Zambia to investigate the impact of solar stoves on biomass fuel use and cooking habits. Participants kept detailed food diaries, recording every ingredient and fuel source used in preparing every dish in every meal every day during the experiment. This produces data on 93,000 ingredients used to prepare 30,000 dishes. Treated households significantly reduce biomass fuel use, cutting emissions by 3–7%, but do not significantly change cooking habits.